NAADP: From Discovery to Mechanism - Walseth, Timothy F.; Guse, Andreas H. (Frontiers in Immunology, 2021)
Nicotinic acid adenine dinucleotide 2‘-phosphate (NAADP) is a naturally occurring nucleotide that has been shown to be involved in the release of intracellular calcium from intracellular stores in a wide variety of cell types, tissues and organisms. Current evidence suggests that NAADP may function as a trigger to initiate a calcium signal that is then amplified by other calcium release mechanisms. A fundamental question that remains unanswered is the identity of the NAADP receptor. Our recent studies have identified HN1L/JPT2 as a high affinity NAADP binding protein that is essential for the modulation of ryanodine receptors and two-pore channels.